Peran katalis dalam reaksi: Dari teori ke aplikasi pada industri kimia - Anggita, Ardina Davi (Maliki Interdisciplinary Journal, 2024)
Catalysis mechanisms involve interactions that improve reaction efficiency, lower the energy needed for the reaction, or open up reaction pathways that wouldn't happen on their own between catalysts and reactants. In the chemical industry, catalysts are vital because they accelerate chemical reactions without being consumed in the process. This article reviews various types of catalysts and their applications, from heterogeneous metal catalysts to noble metal catalysts, across different industrial processes. Catalytic hydrogenation, for example, utilizes catalysts based on Ni, Co, Pd, or Pt to enhance selectivity and efficiency. In the petroleum industry, bifunctional catalysts are used in reforming, hydrocracking, and isomerization processes to produce high-quality products. Additionally, noble metal catalysts such as palladium (Pd) are highly effective in hydrogenating vegetable oils into edible oils, as they can reduce linolenic acid content without affecting other fatty acids. The chemical industry also employs catalysts in ammonia synthesis, with Fe3O4 as the primary catalyst, enabling large-scale ammonia production. Finally, the development of new catalysts like Cu/Cr-spinel allows for the direct hydrogenation of fats into alcohol in a single step, enhancing the efficiency and economy of the process. This article highlights the importance of catalysts in improving productivity and efficiency in industrial processes, as well as the latest innovations in catalyst development for broader applications in the future.